2010
DOI: 10.1111/j.1365-2133.2010.10024.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of primary cutaneous amyloidosis with atopic dermatitis: a nationwide population-based study in Taiwan

Abstract: This is the first nationwide population-based epidemiological study of PCA. We demonstrate that PCA can be associated with other disorders, especially AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
(92 reference statements)
1
27
0
1
Order By: Relevance
“…The diagnosis of PCA is usually straightforward, especially if the morphology and distribution of lesions are typical 1,7 . However, if the area of involvement is located over an unusual site, it becomes difficult to make an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of PCA is usually straightforward, especially if the morphology and distribution of lesions are typical 1,7 . However, if the area of involvement is located over an unusual site, it becomes difficult to make an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan PCA is usually diagnosed clinically due to its common occurrence (mean 1‐year prevalence, 0·98 per 10 000 persons) 6,7 . However, similar clinical pictures do occur in other cutaneous diseases.…”
mentioning
confidence: 99%
“…9 A study in Taiwan showed diabetes to be an important comorbidity among patients with PLCA. 10 Hypothyroidism was seen in three (7.9%) patients. Coexistence of macular amyloidosis and hypothyroidism in Indian women has been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies have reported that PLCA is more common among women. 2,4 Lee et al 18 thought that sampling bias might exist, as most previous studies were based either on personal observation or on data collected from a single hospital. In our study, the number of female and male patients was almost equal, for both the familial and sporadic cases.…”
Section: Discussionmentioning
confidence: 99%